Kausalitas antara Penerimaan, Belanja, dan PDRB pada Kota dan Kabupaten di Indonesia - Haryo Kuncoro (Universitas Islam Indonesia, 2007)
Causality is an important concept in applied econometrics. It helps us to identify the direction which variable is a cause (policy) and which one is an impact. This paper applied the technique of Granger causality to determine the causal relationship between total government expenditures, total tax revenues, and regional income in the case of regencies’/ rmunicipalities’ local government in Indonesia over the period of 1988-2003.Unlike other researchers, this study breaks down the total local government expenditures into operating and capital expenditures. Similarly, the total local government revenues are specified further into local own revenues and intergovernmental transfers (tax & non tax revenue sharing and grant). Using annual panel data, the analysis discovers a firm bidirectional effect from expenditure to revenue. Meanwhile, we found a unidirectional between regional income and grant. It suggests that the preference of controlling either the spending or revenue decisions is conducted both central and local governments to synchronize fiscal performance. Policy implication that could be drawn is that local governments may increase regional economic performance without depending on grants from central government.Keywords: local government, revenue, expenditure and causality